OPTIMALISASI PENGGUNAAN INPUT USAHATANI BAWANG MERAH DI KECAMATAN SENTOLO KABUPATEN KULON PROGO - Ferry Apria Firnando; Susi Widiatmi (Fakultas Pertanian UST, 2018)
This study aims to determine the effect of the use of production factors on production, and determine the economic efficiency of the use of production factors on shallot farming. The basic method of research used is the method of observation and survey with interviews directly with respondents using questioner, then collecting and compiling data, and analyzing and explaining. The method of determining the location of the study was done purposively while the determination of the sample by random sampling. The results showed that the average area of shallot farming was 0.271 ha, and productivity was 9,963.09 kg / ha. Production factors such as land area, labor, seeds, fertilizers, liquid pesticides, solid pesticides simultaneously have a significant effect on the production of shallots farming, but partially only seed and fertilizer factors have a significant effect, while land area, labor, pesticides solid, liquid pesticides have no significant effect. The level of economic efficiency uses factors such as land area production, labor, seeds, fertilizers, liquid pesticides, solid pesticides have not shown efficiency.